Appropriate Timing for Evaluation of the Short-Term Effectiveness of Unicompartmental Knee Arthroplasty - Inui, Hiroshi; Taketomi, Shuji; Yamagami, Ryota; Kono, Kenichi; Kawaguchi, Kohei; Nakazato, Keiu; Takagi, Kentarou; Kage, Tomofumi; Tanaka, Sakae (The Journal of Knee Surgery, 2019)
Satisfactory results have been achieved with unicompartmental knee arthroplasty (UKA) for the treatment of isolated unicompartmental knee disease. However, UKA is associated with a significantly higher rate of revision. There is a tendency toward early revision of UKA for persistent pain because surgeons are not aware that outcomes can spontaneously improve with time. The aim of this study was to identify the time period that patients achieved the highest clinical outcomes following UKA. In total, we examined 72 knees that underwent Oxford UKA. We evaluated the range of motion and clinical results including Knee Society Knee Score, Knee Society Function Score (KSFS), and patient-reported scores using the Knee injury and Osteoarthritis Outcome Score (KOOS) at 1, 2, and 3 years postoperatively. The extension angle showed significant recovery from 1 to 2 years postoperatively, but no significant recovery was observed between 2 and 3 years. The flexion angle at 2 years is larger than at 1 year. The KSFS at 3 years is significantly lower than that at 1 year. The KOOS subscale of activities of daily living showed no significant differences among three periods after operation. The subscales of pain, symptom, sports, and quality of life showed significant recovery from 1 to 2 years postoperatively, but no significant recovery was observed from 2 to 3 years. To evaluate the effectiveness of Oxford UKA, surgeons should obtain clinical outcomes 2 years after the operation.
Keywords: unicompartmental knee arthroplasty; Oxford knee system; patient-reported outcome; unnecessary earlier revision; deterioration with age